Development of multi-platform instrumented force pedals for track cycling - Drouet, J.-M.; Champoux, Y.; Dorel, S. (The Engineering of sport 7, Volume 1, 2008)
The aim of this research was to develop instrumented Force pedals that meet the specific requirements of track cycling. Both pedals are instrumented with eight strain gauges and provide the ability to measure normal and tangential pedalling forces. Rotary encoders are used to determine the angular position of the pedals relative to the crank arm and the angular position of the crank arm relative to the bicycle frame. One original feature is that the instrumented pedals can be fitted with interchangeable pedal platforms: the clipless LOOK CX7 and the Shimano 600 (PD-6400) with a toe-clip and strap for sprint and kilo-metre time trial events. It is therefore possible to measure pedal loads for all track cycling disciplines. The pedals have a very high mechanical resistance in order to withstand the pedal loads produced by track Sprinters which are the highest encountered among all cycling disciplines. Their mechanical design allows the pedals to be installed on any crank arm model without requiring any crank modification. With the data acquisition System attached to a modified Camelbak pack carried by the cyclist, the pedals permit on-track pedal load measurements. Post-processing Software was developed to calculate derived parameters, which include the effective power, the effectiveness index and two components of the total force: the effective force component that is the component normal to the crank arm and the force component in line with the crank arm. The derived parameter calculations and analysis can be done on site for each leg and allow specific qualities to be evaluated (peak power, peak force, etc.). Typical results for these parameters are presented in this paper.